สมบัติของเจลโปรตีนถั่วเหลืองสกัดที่เตรียมโดยแทรนส์กลูทามิเนสและการประยุกต์ใช้ในผลิตภัณฑ์ลูกชิ้นปลา - สุนันทา ทรงกัลยาณวัตร (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The objectives of this study were to examine the properties of soy protein isolate (SPI) gel prepared using microbial transglutaminase (MTGase) and application of SPI and MTGase in fish ball products To study the effect of heating method on the quality of SPI, gel samples were prepared using two levels of SPI (12 and 14%, w/w) and three levels of ACTIVA™ TG-AK (an Ajinomoto s MTGase product) (0.2, 0.4, and 0.6%, w/w). Two different heating methods were used in this study. In heating method 1, SPI suspension was heated until the temperature reached 50℃. MTGase was then added and the temperature was kept constant at 50℃ for 30 more minutes. After that, the temperature was raised to 92℃ and kept constant for 30 minutes. In heating method 2, SPI suspension was heated at 92℃ for 30 minutes. The suspension was then cooled down to 50℃, added with MTGase and kept constant at that temperature for 30 minutes. It was found that heating method 1 produced SPI gel higher in springiness and water holding capacity (WHC) than heating method 2. Meanwhile, the gel strength, hardness and cohesiveness of gels prepared by both methods were similar. Therefore, heating method 1 was selected to be used in future study. In the study of the effect of adding SPI and MTGase addition to fish ball products containing 1.25 or 1.50% (w/w) sodium chloride, 2% mined fish meat in the formula was substituted with binding agent (wheat flour, SPI or wheat flour-SPI mix) and with or without using 0.6% MTGase. SPI was found to help improve gel strength, hardness and WHC of the fish balls. On the other hand, MTGase helped improve gel strength, hardness, cohesiveness, springiness and WHC of the product. Using SPI and/or wheat flour together with MTGase produced fish balls with increased gel strength. Binding agent and MTGase were found to have no effect on the whiteness of the fish balls. From sensory study, the sample with added SPI and MTGase had higher score in hardness, cohesiveness and springiness while fishy flavor, beany flavor, whiteness, gloss, smoothness and saltiness were not significantly different among the samples (p>0.05). Finally, the fish ball samples with added SPI and MTGase were studied for quality while being kept at 4℃. It was found that texture of the fish ball was changed significantly at Day 7-9 of storage. Based on microbiological quality, the fish ball samples had shelf-life up to 17-19 days.